Analisis Pengembangan Sistem Informasi Perpustakaan Digital pada Perpustakaan UINSU - Siti Fauziah; Yusniah Yusniah; Siti Tarissa Ananda Harahap; Alfi Dalillah Aulia. S; Eka Nursah Pitri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
The progress of data systems in the current global era is very meaningful because at this time an institution or industry is not free from the use of PCs as a tool to help process information. Data systems using very advanced and modern PC technology will make it easier for us to carry out information processing that can save time, space and costs. This research uses a qualitative research approach. In terms of terminology for Baydan and Taylor, a qualitative approach is a research method that produces descriptive information in the form of recorded words or words. This research shows that UINSU has carried out the development of a library data system, namely the digital library of UIN North Sumatra. The Digital Library application used by the UIN North Sumatra Medan library is an integrated application where each part of the management of bibliotech collections and consumer services is connected to each other. Keywords: Analysis, Information System Development, Digital Library